1998
DOI: 10.1103/physrevlett.80.4458
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropy of the Critical Magnetic Field in a Ferroelectric Liquid Crystal

Abstract: The angular dependence of the critical magnetic field for the unwinding of the Sm-C ‫ء‬ helix of a ferroelectric liquid crystal has been measured by a deuteron NMR sample tilting technique. A minimum at intermediate angles, resulting in a reentrant Sm-C ‫ء‬ Sm-C Sm-C ‫ء‬ behavior, has been observed. The solitonlike deformation of the helix has a 2p symmetry at a general orientation, whereas it has a p symmetry for the magnetic field parallel to the smectic layers. The results can be interpreted in terms of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 12 publications
0
19
0
Order By: Relevance
“…From this pioneering experiment on the chiral smectogen DOBAMBC-D 21 , the authors could evaluate the anisotropy of the critical magnetic field H C . [19] They also found that solitonlike deformations of the helix have p and 2p symmetry for b = 908 and b ¼ 6 908, respectively. Under these experimental conditions, they observed a phase-transition sequence, wound-unwound-wound SmC * (SmC…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…From this pioneering experiment on the chiral smectogen DOBAMBC-D 21 , the authors could evaluate the anisotropy of the critical magnetic field H C . [19] They also found that solitonlike deformations of the helix have p and 2p symmetry for b = 908 and b ¼ 6 908, respectively. Under these experimental conditions, they observed a phase-transition sequence, wound-unwound-wound SmC * (SmC…”
Section: Introductionmentioning
confidence: 94%
“…This kind of study is very informative and provides an understanding of the phase structure and the stability, and also further supports the Landau-de Gennes theory for the smectic phase. [19] Recently, this type of study was applied to the smectogen 1-methylheptyl 4'-(4''-n-decyloxybenzoyloxy) biphenyl-4-carboxylate (10B1M7) showing an interesting sequence of smectic subphases, which include the antiferroelectric and ferrielectric ones. [21] This work confirms the real potential of 2 H NMR as a sensitive method to understand the structure and the magnetic properties of the ferrielectric mesophases.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some examples include high-T c superconductors [3,4,5], ferroelectric liquid crystals [6,7,8], uniaxial ferroelectrics [9], some types of polymers [10,11,12,13] and magnetic materials [14,15,16,17]. In particular, the confluence of a disordered, a uniformly ordered and a modulated ordered phase characterizes the special critical point associated to this critical behavior, known as the Lifshitz point.…”
Section: Introductionmentioning
confidence: 99%
“…In case of fluorinated compounds, 19 F is also a useful nucleus to investigate. The analysis of the spectral shape of 2 H NMR spectra of liquid crystals provided an excellent and powerful method to investigate the supramolecular structure of liquid crystals, such as in frustrated phases (TGBA, TGBC* and so on) [24] and ferroelectric (SmC*) phases [25]. Dynamic properties, such as molecular reorientational diffusion, translational self-diffusion and collective motions are mainly investigated by specific NMR approaches, such as NMR diffusometry [26] and NMR relaxometry [27] (which requires specific equipment), or by analysing the spin-spin (T 2 ) and spin-lattice (T 1 ) relaxation times (mainly 1 H and 2 H) through specific models [28][29][30].…”
Section: Nmr Basic Principles and Applications To Study Liquid Crystalsmentioning
confidence: 99%